2018
DOI: 10.1002/jat.3758
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive lipid profiling of bleomycin‐induced lung injury

Abstract: Drug‐induced lung injury is an adverse effect of drug treatment that can result in respiratory failure. Because lipid profiling could provide cutting‐edge understanding of the pathophysiology of toxicological responses, we performed lipidomic analyses of drug‐induced lung injury. We used a mouse model of bleomycin‐induced lung injury and followed the physiological responses at the acute inflammatory (day 2), inflammatory‐to‐fibrosis (day 7) and fibrosis (day 21) phases. The overall lipid profiles of plasma, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Further, it was reported that PI binds to the CD14 plasma membrane and prevents monocyte activation by bacterial lipopolysaccharides (40). Saito et al (15) conjectured that high levels of PG and PI counteract inflammation and thus ameliorate BLM-induced lung injury . Our study showed that PG and PI were more increased in the Inter Group than the Model Group , and D-4F can decrease inflammation in experimental asthma and influenza infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it was reported that PI binds to the CD14 plasma membrane and prevents monocyte activation by bacterial lipopolysaccharides (40). Saito et al (15) conjectured that high levels of PG and PI counteract inflammation and thus ameliorate BLM-induced lung injury . Our study showed that PG and PI were more increased in the Inter Group than the Model Group , and D-4F can decrease inflammation in experimental asthma and influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…The way of induction of lung fibrosis is as the article described (15). To induce pulmonary fibrosis, the mice were anesthetized with pentobarbital sodium salt and given a single intratracheal instillation of 60 μL (2 mg/kg) or PBS as a control.…”
Section: Induction Of Lung Fibrosismentioning
confidence: 99%
“…Similarly, human studies have reported seemingly contradictory data regarding the direction and magnitude of change in surfactant lipids during disease, and there is no agreement on a mechanism for the observed alterations [67] (Table 1). In some studies, increased levels of PC, cholesterol and bis monoacyl phosphoglycerate (BMP) in whole lung tissue and of all lipids in BAL up to 21 days after bleomycin have been reported [131]. Intratracheally administered bleomycin increased cholesterol and free FA in BAL in rats, and this was associated with increased collagen deposition and epithelial cell proliferation, elastic recoil and surface tension of the BAL.…”
Section: Lipids In Interstitial Lung Disease and Idiopathic Pulmonarymentioning
confidence: 99%
“…The NLRP3inflammasome consists of three elements including the NLRP3, procaspase 1 and the apoptosis speck-like protein (ASC) containing a caspase recruitment domain (CARD), which links NLRP3 with procaspase 1 (Robert et al, 2016). In order to generate full activation of the inflammasome complex usually two independent signals are needed (Figure 3): (1) a NFκβ priming signal TLR-4 signaling [enhanced by lipopolysaccharide (LPS) or oxidized phospholipid species] or the presence of cholesterol crystals (Bauernfeind et al, 2009;Ertunc and Hotamisligil, 2016;Fessler and Summer, 2016;Nakayama, 2018;Saito et al, 2019) and;…”
Section: Inflammatory Response Under Impaired Lung Mechanics -Where Smentioning
confidence: 99%